Task-dependent influences of attention on the activation of human primary visual cortex - Watanabe, Takeo (The National Academy of Sciences, 1998)
There has been a good deal of controversy over whether attention influences area V1—the first cortical area onto which information from the retina is projected. Attention to motion has been found to modulate monkey area MT and the human homolog of MT/MST. Here we show that activation of V1 by attention to motion is task dependent. Our stimulus consisted of a group of translating random dots superimposed over another group of random dots executing expansion motion. Subjects were instructed to pay attention selectively to the translation, expansion, or neither in particular (passive condition). The activity in the human MT/MST homolog measured by functional magnetic resonance imaging (fMRI) was significantly higher in both the translation and the expansion conditions than in the passive condition, while the activity in area V1 was significantly higher only in the translation condition. These results show that attention to motion modulates area V1, and more interestingly that high-level cognitive processing such as attention may directly or indirectly determine the retroactive extent of feedback within the motion pathway in a manner dependent on the type of motion attended.